Changes in composition, cellulose degradability and biochemical methane potential of Miscanthus species during the growing season. (July 2017) - Peng, Xiaowei; Li, Chao; Liu, Jing; Yi, Zili; Han, Yejun
Highlights: Miscanthus composition changed slightly during growing season. The BMP correlated positively to the cellulose degradability. Prolonged growth time led to a decrease in BMP and the cellulose hydrolysis rate. Cellulose degradability impacts on the economic benefit from Miscanthus . Abstract: The composition, cellulose degradability and biochemical methane potential (BMP) of M. sinensis, M. floridulus, Miscanthus × giganteus and M. lutarioriparius were investigated concomitantly at different growth/harvest times during their growing season. For all the four species, there was only a slight change in the compositional content. Meanwhile there was a huge change in the BMP values. At the growth time of 60 days the BMPs ranged from 247.1 to 266.5 ml g −1 VS. As growth time was prolonged, the BMPs decreased by 11–35%. For each species, the BMP was positively correlated to the cellulose degradability with the correlation coefficients (R 2 ) ranging from 0.8055 to 0.9925. This suggests that besides the biomass yield, it is justifiable to consider cellulose degradability when selecting the suitable harvest time for biofuels production from Miscanthus, especially in tropical and subtropical regions where Miscanthus can be harvested twice or more within a year.